Green Banking Prospects in Bangladesh - Rahman, Md. Mustafizur; Ahsan, Md. Ali; Hossain, Md. Motahar; Hoq, Meem Rafiul (Asian Business Review, 2013)
Green banking is the operation of the banking activities giving especial attention upon the social, ecological and environmental factors aiming at the conservation of nature and natural resources. Banks can be green through bringing changes in six main spheres of banking activities. Those are Change in Investment Management, Change in Deposit Management, Change in House Keeping, Change in the Process of Recruitment and Development of Human Capital, Corporate Social Responsibility (CSR), and Making Consciousness Among Clients and General Mass. Such an initiation can ensure a safe residence for upcoming generation. Bangladesh Bank has already issued circulars regarding this. Banks have already been asked to make their own green banking policy. Now we only need raising voice, keeping hand over hands, thinking in positive way and working in collective manner to make this a true.
Keywords: Green Banking; Green Policy; Green Products